Baryon violating first order phase transitions and gravitational waves - Andrea Addazi (Physics Letters B)
We propose a scenario in which the matter-antimatter asymmetry arises following the post-electroweak spontaneous breaking of baryon (B) number symmetry. This B-symmetry undergoes a first-order phase transition, which can be sufficiently violent to generate gravitational waves across a broad parameter space. Specifically, we explore a concrete realization of this mechanism that induces a Majorana mass for the neutron, rather than the neutrino. We demonstrate that this model exhibits rich phenomenology, including the generation of gravitational waves from baryon first-order phase transitions (B-FOPTs) and implications for neutron-antineutron oscillations.